A voz de Roberto Carlos: avaliação perceptivo-auditiva, análise acústica e a opinião do público - Oliveira, Sonia Cristina Coelho de (2007)
Introduction: in Brazil, Roberto Carlos has been studied in many areas of knowledge, among them History and Social Psychology due to his relevance as an interpreter and musical and social phenomenon. The singer is considered a bestselling artist, being able to reach an audience of various social, economical and cultural classes. Objective: to analyse Roberto Carlos s voice by perceptive-hearing evaluation, acoustic analysis and the audience's opinion. Method: a perceptivehearing evaluation of voice was performed of two selected songs from each decade (60 to 90), by six evaluation judges (speech therapists and vocal teachers); the acoustic analysis of pieces of the songs DETALHES and EMOÇÕES, by the researcher, and a questionary with two questions, to have a sample of the population of the city of Sao Paulo (group 1-G1) and another to the fans of the singer (group 2-G2) who belong to the communities on-line on orkut. Results: in relation to the perceptive-hearing analysis of the voice, the parameters most referred in the four decades were: adequate respiratory-speech, medium pitch for the shrill, adequate loudness, precise articulation, soft vocal attack, vocal resonance with nasal compensatory focus, chest modal register, brilliance and projected voice, vibrato predominantly absent, medium tessitura and adjusted vocal quality. The quality of the recording was related as reasonable and the characteristics related to the recording showed variable: jovial and immature voice in the sixties; fluent interpretation, with the emission soothed in the seventies; variation in the vocal parameters in the eighties and showing discrete vibrato with characteristics of tremor, compressed and with alteration in the dynamics, nevertheless mature and introspective in the nineties. The measures of acoustic analysis indicated a bigger variation of the harmonics in the song EMOÇÕES. The contour of the pitch and the amplitude coherent with the melody, f0 without variation and vibrato predominantly absent were found in two pieces of music. F1, F5 reduced; F2, F3, F4 increased; a bigger prolongation and accentuation of the vowels in the song DETALHES were observed and F1, F2 reduced; F3, F4 with little variation and F5 increased in the song EMOÇÕES. The questionary of G1 proved statically that 70,38% of the citizens like the singer, from this total, 76,15% belong to the female and 86,54% are between 51 and 60 years old. In terms of background and superior income made evident that the individual qualified the singer s voice in a negative way. From the 70,38% of the individuals that like the singer, 18,03% like him because of the songs. On the other hand from the 29,62% of the individuals that don t like the singer, 33,77% don t like him because of his songs. The questionary of G2 showed that there wasn t meaningful statistic for these variables, but it was evident that this group presented levels of income and background superior to G1. Conclusion: the results enabled to show that there were few variations in the voice of the singer Roberto Carlos in the elapsing of his artistic trajectory, more evident in the decades of 60 to 70 coherent with the styles adopted and age, keeping similar in the years 80 and 90. Notwithstanding, for the audience (G1 and G2), Roberto Carlos s voice isn t the predominant factor whether to like him or not, but his repertory, that is the content of his songs that is simbolized by the hearer